Wiktoriańska katedra sztuki - Antonowicz, Anna (Er(r)go. Teoria - Literatura - Kultura, 2012)
Anna Antonowicz A Victorian Cathedral of Art The Victorian epoch was a period of great admiration for- and revival of medieval, particularly gothic, design. Although the Victorian South Kensington Museum (today Victoria and Albert Museum) did not replicate gothic architecture, the objectives and character of its interiors show significant parallels to it in terms of the impact which the gothic cathedral would exert on its visitors. The gothic cathedral would appeal to the eye by its grand scale, majestic beauty and opulent decoration. These three features constituted an impressive―and effective―instrument in the diffusion of Christian dogmas and teachings to all classes of the medieval feudal society. A similar mechanism pertaining to the treatment of the interior as a didactic iconographic text was made use of in the case of South Kensington Museum in the mid-Victorian period. The application of such a mechanism helped emphasise the authoritative character of the Museum as an institution responsible for the reform of British decorative art and art education, as well as for the improvement of artistic tastes of all classes of the Victorian society in Britain. In other words, the interior iconographic programme transformed the South Kensington Museum into an institution of an exceptional public missionary role, a cathedral among other Victorian temples of art.